Faktor-Faktor yang Mempengaruhi Kecenderungan Kecurangan Akuntansi Pada LPD di Kabupaten Badung: Peran Keefektifan Pengendalian Internal - Putri, Ni Wayan Ayu; Suartana, I Wayan (E-Jurnal Akuntansi, 2022)
The purpose of this study was to analyze the factors that influence the tendency of accounting fraud in LPDs in Badung Regency with the effectiveness of internal control as a moderating variable. This research was conducted in LPD in Badung Regency, the number of samples used were 93 LPD supervisors with purposive sampling method. Data was collected using a survey approach with the research instrument used was a questionnaire. The data collected was then analyzed using multiple linear regression analysis techniques. The results showed that there was a negative influence between the suitability of compensation for the tendency of accounting fraud, information asymmetry had no effect on the tendency of accounting fraud, internal control had a negative effect on the tendency of accounting fraud, internal control was able to moderate the effect of the suitability of compensation on the tendency of accounting fraud, internal control was not able to moderate the effect of information asymmetry on the tendency of accounting fraud. Keywords : Compensation Suitability; Information Asymmetry; Internal Control; Trends in Accounting Fraud.